Changing competition models in market economies: The effects of internationalisation, technological innovations and academic expansion on the conditions supporting dominant economic logics - Richard Whitley (The University of Manchester, Manchester Business School, 2009)
Different ways of competing in markets came to dominate particular sectors, regions and national market economies in the postwar period as a result of variations in market conditions, technological regimes and institutional contexts. These varied in terms of production volumes, basis of competition and rapidity of response to changes in demand and technologies. They were supported by six features of product, labour and capital markets as well as by particular characteristics of technological regimes. Since the breakdown of the Bretton Woods system, increased market internationalisation, the collapse of state socialism, radical technological change and the expansion of incomes, education and science have altered these features. Consequently, levels of support for many of the components of established competition models have changed, as has the dominance of these models in particular areas.
Keywords: 330